Beyond single stories : changing narratives for a changing world - Allen, Amy E.; Kavanagh, Anne Marie; Cassaithe, Caitríona Ní (Social science education consortium book series., 2024)
"Every social studies curriculum tells a story. It is increasingly apparent that new stories are needed to guide us through the multiple and intersecting crises that have come to define our times. This accessible volume supports student teachers, teachers, and teacher educators to engage critically with the stories that social studies curricula tell and neglect to tell, particularly those that relate and contribute to the root causes of contemporary social and ecological injustices. A balanced and inclusive curriculum necessitates a broad range of stories and perspectives, not just the master narratives of dominant groups. Incorporating a range of pedagogical approaches and spanning a diversity of themes, from representations of Africa in Chinese textbooks, to slavery and the American civil rights movement, to refugees and the role of indigenous knowledge systems in addressing climate breakdown, this volume includes and creatively engages with previously marginalized and silenced stories and perspectives. Both practical and theoretical in its approach, it seeks to provoke, meaningfully support, and inspire educators to incorporate alternative stories or counter-narratives into their social studies teaching. This unique volume is essential reading for student teachers, teachers, teacher educators as well as anyone interested in inspiring children and young people to be open-minded, critically engaged, and empathetic agents of change, committed to addressing real-world social and ecological injustices"--